Chondrocyte-based approaches and scaffolds for knee cartilage injuries - an international Delphi consensus statement - Grant H. Cabell; Eoghan T. Hurley; Richard M. Danilkowicz; Mats Brittberg; David C. Flanigan; Elizaveta Kon; Bert R. Mandelbaum; Stefan Marlovits; Norimasa Nakamura; Jocelyn R. Wittstein; Alison P. Toth (Elsevier, 2024)
Introduction: Articular cartilage injuries of the knee are a complex and challenging clinical pathology. Objectives: The purpose of this study was to establish consensus statements via a Delphi process on chondrocyte-based cartilage (CBC) approaches and scaffolds for cartilage injury. Methods: A consensus process on knee cartilage injuries utilizing a modified Delphi technique was conducted. Seventy-nine surgeons across 17 countries participated in these consensus statements. Ten questions were generated on chondrocyte-based approaches and scaffolds, with 3 rounds of questionnaires and final voting occurring. Consensus was defined as achieving 80% to 89% agreement, whereas strong consensus was defined as 90% to 99% agreement, and unanimous consensus was defined as 100% agreement with a proposed statement. Results: Of the 10 total questions and consensus statements on CBC repair developed from 3 rounds of voting, 1 question achieved unanimous consensus, 6 achieved strong consensus, 2 achieved consensus, and 1 did not achieve consensus. Conclusions: The statements that achieved strong or unanimous consensus were related to indication and relative indications for CBC repair, harvesting site for chondrocytes, differentiating healthy and unhealthy cartilage, sizing defects, minimizing complications, and orthobiologics utility. These consensus statements regarding chondrocyte-based approaches and scaffolds for cartilage injury will hopefully assist clinicians in the management of this challenging pathology.